The Impact of Financial Inclusion Initiatives: A Meta-analysis - Biru, Ashenafi; Molla, Alemayehu (KDI School of Public Policy and Management, 2021)
Developing inclusive financial system is an important policy intervention to create opportunities for e economic development, reduce poverty and improve the livelihood of the poor. Despite the growing and focused research interest on financial inclusion, empirical findings on the role of financial inclusion to accelerate economic development are mixed and inconclusive. This limits the building of a cumulative and conclusive evidence base to inform policies and strategies to address financial exclusion. The purpose of this study is to provide a comprehensive synthesis of empirical studies on the impact of financial inclusion and unravel the sources of inconsistencies in financial inclusion studies. The study extracts and analyzes, through meta-regression analysis, the dependent and independent variables and estimates from 67 empirical studies. The results indicate that empirical research on financial inclusion conflates two related but distinct concepts of participation of the poor in the formal and informal financial sectors. There is also inconsistent measurement of financial inclusion and outcome indicators. Overall, regardless of the inconsistency in measurement, financial inclusion has a statistically significant positive effect on household livelihood outcomes. We note that the inconsistent in measurement and quality of the empirical evidence raises concerns about the reliability of the overall findings.